Analisis Penghentian Pengakuan Aset Tetap Pada PT Central Light Concrete Berdasarkan SAK-ETAP - Eka Yuni Amaliya; Sjamsul Hidayat; Andrianto Andrianto (BALANCE: Economic, Business, Management and Accounting Journal, 2019)
ABSTRACT This study aims to determine the analysis of the termination of fixed asset recognition at PT Central Light Concrete based on SAK-ETAP. The method in the study is descriptive with a qualitative approach, namely by providing an overview of the analysis of the termination of fixed assets at PT Central Light Concrete based on SAK-ETAP. In conducting this research, the author uses data collection methods by means of interviews, observation, and documentation.The results of the study indicate that when a fixed asset usage discontinuation occurs because it is damaged or not in accordance with the new production concept, PT Central Light Concrete has not terminated the recognition of fixed assets. PT Central Light Concrete still charges the depreciation of these fixed assets in the income statement and recognizes those fixed assets in the balance sheet.The conclusion in this study is that PT Central Light Concrete has not implemented the termination of recognition of damaged fixed assets or fixed assets that are no longer used before the useful life is used up and still records the depreciation of the fixed assets. This is not in accordance with SAK-ETAP where the entity must stop recognizing fixed assets when released or when no future economic benefits are expected from their use or disposal. Gains or losses arising from derecognition of property and equipment must be recognized in the income statement at the end of the period. Fixed assets that have been derecognized must also be written off from the company's fixed assets list and balance sheet at the end of the period. It is intended that the financial statements presented can help the Management of PT Central Light Concrete in making decisions or policies.Keywords                   : Fixed Assets, Termination of RecognitionCorrespondence to       : andrianto914@yahoo.com ABSTRAK  (bahasa indonesia)Penelitian ini bertujuan untuk mengetahui analisis penghentian pengakuan aset tetap pada PT Central Light Concrete berdasarkan SAK-ETAP.Metode dalam penelitian adalah deskriptif dengan pendekatan kualitatif yaitu dengan memberikan gambaran mengenai analisis penghentian pengakuan aset tetap pada PT Central Light Concrete berdasarkan SAK-ETAP. Dalam melakukan penelitian ini, penulis menggunakan metode pengumpulan data dengan cara wawancara, observasi, dan dokumentasi.Hasil penelitian menunjukkan bahwa saat terjadi penghentian pemakaian aset tetap karena rusak atau tidak sesuai dengan konsep produksi yang baru PT Central Light Concrete belum melakukan penghentian pengakuan aset tetap. PT Central Light Concrete masih membebankan penyusutan aset tetap tersebut dalam laporan laba rugi dan mengakui aset tetap tersebut dalam laporan neraca.Kesimpulan dalam penelitian ini adalah PT Central Light Concrete belum menerapkan penghentian pengakuan aset tetap yang rusak atau aset tetap yang tidak dipakai lagi sebelum umur manfaatnya habis dan masih mencatat penyusutan aset tetap tersebut. Hal ini tidak sesuai dengan SAK-ETAP di mana entitas harus menghentikan pengakuan aset tetap pada saat dilepaskan atau ketika tidak ada manfaat ekonomi masa depan yang diekspektasi dari penggunaan atau pelepasannya. Keuntungan atau kerugian yang timbul dari penghentian pengakuan aset tetap harus diakui dalam laporan laba-rugi di akhir periode. Aset tetap yang telah dihentikan pengakuannya juga harus dihapuskan dari daftar aset tetap perusahaan dan laporan neraca di akhir periode. Hal ini bertujuan agar laporan keuangan yang disajikan dapat membantu Manajemen PT Central Light Concrete dalam pengambilan keputusan atau kebijakan.Kata kunci                  : Aset Tetap, Penghentian PengakuanKorespondensi             : andrianto914@yahoo.com